(untitled) (Indian Journal of Arid Horticulture, 2025)
Ladakh, the northern part of India located in the Trans Himalayas at an altitude of 11,500 ft. above MSL. The climate of cold arid region is a blunt of arctic and desert climates characterized by long severe winter where mercury drops down to -40°C while summer is short hot with cooler nights and dries with scanty rainfall. Garlic (Allium sativum) is the second most widely used cultivated vegetable Allium sativum after onion it is being used in several food preparations. This is an essential part of the fresh vegetable provided to the troops of Ladakh due to its high medicinal value. According to the ration scale of the Army, it is provided at a scale of 20gm/person/day (Sharma et al., 2009). If the same scale used, there is an average requirement of 1800 MT fresh Garlic annually in Ladakh region for local population as well as army deployed in this sector (FRL Report, 2003).